Pengaruh Model Pembelajaran RADEC (Read, Answer, Discuss, Explain, Create) terhadap Hasil Belajar dan Kemampuan Pemecahan Masalah Siswa pada Materi Fluida Statis di Kelas XI SMA Negeri 5 Binjai - Jonny Haratua Panggabean; Nando Seftian Barus (Mataram University, 2026)
Study objectives included identifying the relationship between and improvements to students' problem-solving abilities and learning outcomes in static fluid material after using the Read, Answer, Discuss, Explain, and Create (RADEC) learning model, and analyzing the model's effect on these two variables. Using a control group design with pre- and post-tests, this study was quasi-experimental. The research included all eight classes of students in Grade XI at SMA Negeri 5 Binjai. The research samples were divided into two groups according to the results of a basic random sampling procedure. Read, Answer, Discuss, Explain, and Create (RADEC) was the learning methodology used in Class XI Science 1 while conventional learning was used in Class The experimental group's average pre- and post-test scores for learning outcomes were 45.91 and 79.70, respectively, whereas the control group's average scores were 44.85 and 62.42. Students' problem-solving abilities were averaged out in the experimental class at 78.06 on the posttest and 44.67 on the pretest, compared to 68.30 in the control class. Analyzes such as MANOVA, N-gain, and correlation tests were applied to the data. Results showed that when compared to traditional methods of instruction, the RADEC learning model significantly improved students' capacity to understand and solve problems. The experimental group also outperformed the control group in terms of the N-gain measures used to measure improvements in learning outcomes and problem-solving abilities. Students' problem-solving skills were positively correlated with their learning outcomes, according to the results of the correlation test.